211k views
13 votes
Simplifying and solving rational p

Simplifying and solving rational p-example-1

1 Answer

14 votes

Answer:

A. x = 0, 14

B. x = 12, -2

Explanation:

A.

2x - 3 x + 6

/ = /

x + 1 x - 2

2x^2 - 7x + 6 = x^2 + 7x + 6

- x^2 - 7x - 6 - x^2 - 7x - 6

x^2 - 14x = 0

( x + 0 ) = 0 ( x - 14 ) = 0

x = 0, +14 +14

x = 14

-----------------------------------------------------

B.

2 x

/ = /

x 5x + 12

x^2 = 2( 5x + 12 )

x^2 = 10x + 24

- 10x - 24 - 10x - 24

x^2 - 10x - 24 = 0

( x - 12 ) = 0 ( x + 2) = 0

+12 +12 -2 -2

x = 12, x = -2

I hope this helps!

User Phil Calvin
by
5.5k points